Clive V. Thomas. Dependence and Transformation : The Economics of the Transition to Socialism, Nueva York, Monthly Review Press, 1974. 327 p. - Graizbord, Boris (Estudios Demográficos y Urbanos, 1979)
Clive, V. Thomas, Dependence and Transformation: The Economics of the Transition to Socialism, Nueva York, Monthly Review Press, 1974.